Replacement of porcelain fused to metal crown with e.max lithium disilicate crown (case report): Penggantian mahkota tiruan porcelain fused to metal dengan mahkota tiruan e.max lithium disilicate (laporan kasus) - Melisa; TA Mahendra (Makassar Dental Journal PDGI Makassar, 2021)
Background: Even though porcelain fused to metal (PFM) crown is the golden standard in dentistry, it still has a major disad-vantage, such as unaesthetic metallic seen. Resolving those type of problems, an all-ceramic restoration was chosen to improve aesthetic outcome especially in the anterior regions of the mouth. Objective: This article reports the replacement of old PFM crowns in central incisors with poor design with lithium disilicate crowns. Case: A 25-years-old female came to Prosthodontic Clinic RSKGM Universitas Indonesia with complaints of chipping PFM crowns in central incisors with poor shape and colour. Conclusion: Patient’s aesthetic expectations were successfully met through selection of lithium disilicate crowns.